Cardiovascular event rates and healthcare resource utilisation among high‐risk adults with type 2 diabetes mellitus in a large population‐based study. Issue 2 (February 2015) - Fox, K. M.; Wu, Y.; Kim, J.; Grandy, S.
Summary Objective This study ascertained the incidence and resource utilisation of non‐fatal myocardial infarction (MI), stroke, coronary bypass surgery or angioplasty among adults with type 2 diabetes mellitus (T2DM) at high risk for cardiovascular disease (CVD) over 3 and 5 years. Methods Respondents from the US, population‐based SHIELD study with T2DM and at cardiovascular risk were stratified into an established CVD cohort and a risk factors cohort. Proportion of respondents self‐reporting a new MI, stroke or revascularisation was calculated. Multivariate discrete logistic hazards models were utilised. Results Incidence rate in the established CVD cohort (n = 1198) was 26.3% over 3 years (31.2%, 5 years) and in the risk factors cohort (n = 924) 18.8% over 3 years (26.0%, 5 years). Healthcare resource use was significantly greater among respondents who had a new CV event than among those not experiencing an event (p < 0.001). Conclusions Individuals with T2DM at risk for CVD had a high incidence of CV events in this large US study, which represents a significant burden on the healthcare system.